Precise genome editing in the silkworm Bombyx mori using TALENs and ds- and ssDNA donors – A practical approach. (November 2016) - Takasu, Yoko; Kobayashi, Isao; Tamura, Toshiki; Uchino, Keiro; Sezutsu, Hideki; Zurovec, Michal
Abstract: Engineered nucleases are able to introduce double stranded breaks at desired genomic locations. The breaks can be repaired by an error-prone non-homologous end joining (NHEJ) mechanism, or the repair process can be exploited to introduce precise DNA modifications by homology-directed repair (HDR) when provided with a suitable donor template. We designed a series of DNA donors including long dsDNA plasmids as well as short ssDNA oligonucleotides and compared the effectiveness of their utilization during gene targeting with highly efficient transcription activator-like effector nucleases (TALENs). While the use of long dsDNA donors for the incorporation of larger DNA fragments in Bombyx is still a problem, short single-stranded oligodeoxynucleotides (ssODNs) are incorporated quite efficiently. We show that appropriately designed ssODNs were integrated into germ cells in up to 79% of microinjected individuals and describe in more detail the conditions for the precise genome editing of Bombyx genes. We specify the donor sequence requirements that affected knock-in efficiency, and demonstrate the successful applications of this method of sequence deletion, insertion and replacement in the Bombyx genome. Graphical abstract: Highlights: Long dsDNA as well as short ssDNA oligonucleotides were tested as donors for precise genome editing. The frequency of individuals carrying the ssODNs successfully integrated into the germline was up to 79% for small indels. Precise insertions of up to 35 nt and a deletion of 1.9 kb in length were also observed with practically usable frequencies. Improvements in ssODNs design that increase the efficiency of integration are suggested.